Evaluation of Partnership Management of Vocational Education on Vehicle Engineering Department with the Industry - Sudrajat, Surya Catur; Amardhiana, Amardhiana; Lestari, Yoni Dwi; Joko, Joko; Basuki, Ismet (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The development of the era in the industrial revolution 4.0 has caused many changes in the sectors of life that have an impact on human activities. In order to fulfill the competency of the 21st century industrial world, humans are required to be able to compete in all fields. This adaptability is a real challenge in the world of education, especially vocational education. Vocational education must collaborate with the industrial world to continue to follow the development of the era. This study aims to assess the management of partnerships between the world of education and the industrial world. This CIPP Evaluation Research uses a mix method research model, with a concurrent triangulation strategy design. The study was conducted in April-May 2025 involving teachers, industry players and students from the light vehicle engineering department at SMK in Magetan City. The data collection method used questionnaires and interviews. The results of the study showed that the aspects of Context, Input, Process and Product received good assessments from schools and industry, only improvements were needed in the facilities and infrastructure that were still considered lacking by schools that were in accordance with industry standards, and the intensity of interaction and communication between schools and industry which was still lacking. Monitoring and evaluation from schools were still considered low intensity.